The Immobilization Of Candida Rugosa Lipase On The Chitosan Beads - Mohd Romli, Muliati (Universiti Sains Malaysia, 2018)
The immobilized enzyme is an important catalyst which used mainly to increase the rate of reaction. One of the methods to immobilize the enzyme is by covalent bonding. In the present research, Candida rugosa (C. rugosa) lipase was successfully immobilized by the method of covalent bonding onto activated chitosan beads. The immobilization of lipase on the chitosan beads was confirmed by determining lipase activity during hydrolysis of a standard substance. The effect of lipase and glutaraldehyde (GA) concentrations on immobilization yield and activity yield were investigated. In general, the concentration of GA and lipase gave significant effect on immobilization yield and activity yield. As the GA concentration increase, the activity yield was decreased, while as the lipase concentration increase, the immobilization yield relatively decrease. The highest immobilization yield was 77.335 %, were achieved at 6 % of GA and 0.001 g/mL of C. rugosa lipase. After that, the highest activity was 50.3613 IU, where obtained at 2 % of GA and 0.010 g/mL of C. rugosa lipase. The optimization of immobilization process parameters was carried out via Respond Surface Method (RSM). It has been found that the most optimal condition for immobilization was at 4 % glutaraldehyde concentration and 0.005 g/mL of C. rugosa lipase which gave 65.14 % of immobilization yield and 32.84 IU of unit activity. The immobilized lipase was used repeatedly in the hydrolysis reaction. It was found that the immobilized enzyme was more stable and has the ability to be used multiple times. Therefore, immobilization of lipase onto activated chitosan support was feasible and it can be reused for 7 times. However, the activities reduce to 53.67 % after the 7th cycle.